Faktor-Faktor Yang Mempengaruhi Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Kabupaten Bener Meriah - Sopiandi, Sopiandi; HS, Nurlaely; Iriyanti, Maulina; Elyarianti, Elyarianti; Muzaffar, Muzaffar (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Stunting is a condition where the body experiences growth failure caused by chronic malnutrition, causing stunting sufferers to have a body shorter than the standard for their age. Stunting is caused by several factors, both from the mother’s pregnancy until the birth of the baby. This study aims to determine the factors that influence the incidence of stunting in toddlers in the Bener Meriah Regency Community Health Center Working Area. The research method used a cross-sectional. The population was 888 mothers who had toddlers. A sample of 88 people, using a simple random sampling technique. Data analysis used the chi-square test. The results of the chi-square test correlation analysis obtained a significant value of the LBW factor of 0.002 <0.05, the exclusive breastfeeding factor of 0.010 <0.05, the IMD factor of 0.130>0.05, the weaning age factor of 0.002 <0.05, and the complementary feeding factor of 0.000 <0.05. Therefore, it can be concluded that there is a significant influence between low birth weight (LBW), exclusive breastfeeding, weaning age, and complementary feeding on stunting. Furthermore, there is no significant influence between early initiation of breastfeeding (IMD) and stunting in toddlers in the Bener Meriah Regency Community Health Center (Puskesmas) working area. Parents are expected to prepare for pregnancy well, by improving their knowledge, social, and economic well-being to prevent the continued increase in stunting